AN INNOVATION-BASED ASSESSMENT MODEL FOR BIPA: EXAMINING INTEGRATED LISTENING AND SPEAKING EVALUATION - Novi Haryanti; Ribut Wahyu Eriyanti; Hari Sunaryo (Indonesian EFL Journal, 2026)
This study proposes and empirically tests an innovation-based evaluation model for Bahasa Indonesia bagi Penutur Asing (BIPA) assessment by examining the effects of listening–speaking integration, authentic communication tasks, and assessment feedback quality on evaluation model quality. Employing a quantitative explanatory design, data were collected from BIPA learners and analyzed using Partial Least Squares Structural Equation Modeling. The results indicate that authentic communication tasks and assessment feedback quality have significant positive effects on evaluation model quality, whereas listening–speaking integration does not show a significant direct effect. The proposed model explains 63.5% of the variance in evaluation model quality, demonstrating strong explanatory power. These findings highlight that innovation in BIPA assessment is primarily driven by task authenticity and meaningful feedback rather than skill integration alone. This study contributes to communicative competence-oriented assessment by clarifying the relative roles of authenticity, feedback, and integrated skills in strengthening the pedagogical relevance and effectiveness of BIPA evaluation models.